Research progress of circRNAs in bone-related diseases - Hua, Xianming; Yu, Lingfeng; Zhu, Hao; Zhu, Yan; Fan, Gentao; Zhou, Guangxin (Frontiers in Oncology, 2025)
Circular RNAs (circRNAs) are non-coding RNAs that exist naturally in various eukaryotic organisms. The majority of circRNAs are produced through the splicing of exons, although there are a limited number that are generated through the circularization of introns. Studies have shown that circRNAs play an irreplaceable role in the pathogenesis, disease progression, diagnosis, and targeted therapy of motor system tumors (osteosarcoma), metabolic diseases (osteoporosis), and degenerative diseases (osteonecrosis of the femoral head, osteoarthritis, intervertebral disc degeneration). This review summarizes the advancements in circRNA detection techniques and the research progress of circRNAs in orthopedic diseases.